MUSIK ROCK ALTERNATIF DALAM KALANGAN REMAJA: ISU SUB-BUDAYA REMAJA DAN PEMBANGUNAN INSAN DALAM ERA GLOBALISASI - Rokiah Ismail (Universitas Andalas, 2017)
The debate on the involvement of youth in music is not a new topic in the discourses on youth and life styles. The article discusses a research work on a group of Malay urban youth in Malaysia who were involved in underground rock music and the activities associated with it. The qualitative research based especially on a collection of primary data analyzes the elements of the underground rock music and the dynamics of its particular subculture. It touches both the ideological and behavioral aspects related to the youth’s involvement in underground rock music. The findings show that a group of Malay urban youth favors this type of music not only as a source of entertainment, but also underground rock music provides them with a channel to express their specific feelings, sentiments, and opinions associated with their specific life experiences, both as individuals and as a group within the society. Their involvement is very much related to factors such as the particular characteristic features of the music and the social elements or issues touched upon such as subjects on social consciousness, generational identity, individual’s creativity, social status, choice and freedom. For many youth, these elements have significant meanings for their daily living experiences and lifestyles and they provide them with a strategy needed to position themselves in a certain niche for survival as a group in the changing society like Malaysia.